The De Novo Genome Assembly of Olea europaea subsp. cuspidate, a Widely Distributed Olive Close Relative - Wu, Tao; Ma, Ting; Xu, Tian; Pan, Li; Zhang, Yanli; Li, Yongjie; Ning, Delu (Frontiers in Genetics, 2022)
The Olive complex, comprised of six subspecies, are valuable plants for global trade, human health, and food safety. However, only one subspecies (Olea europaea subsp. europaea, OE) and its wild relative (Olea europaea subsp. europaea var. sylvestris, OS) have genomic references, hindering our understanding on the evolution of this species. Using a hybrid approach by incorporating Illumina, MGI, Nanopore, and Hi-C technologies, we obtained a 1.20 Gb genome assembly for the olive subspecies, Olea europaea subsp. cuspidate (OC) with contig and scaffold N50 values of 5.33 Mb and 50.46 Mb, respectively. A total of 43,511 protein-coding genes were predicted from the genome. Interestingly, we observed a large region (37.5Mb) of “gene-desert” while “LTR-hotspot” in chromosome 17. The gene origination analyses revealed a substantial outburst (19.5%) of gene transposition events in the common ancestor of olive subspecies, suggesting the importance of olive speciation in shaping the new gene evolution of OC subspecies. The divergence time between OC and the last common ancestor of OE and OS was estimated to be 4.39 Mya (95% CI: 2.58 – 6.23 Mya). The pathways of positively selected genes of OC are related to metabolism of cofactors and vitamins, indicating the potential medical and economic values of OC for further research and utilization. In summary, we constructed the de novo genome assembly and protein-coding gene pool for Olea europaea subsp. cuspidate (OC) in this study, which may facilitate the breeding applications of improved olive varieties from this widely distributed olive close relative.